2023
DOI: 10.1158/0008-5472.can-22-2585
|View full text |Cite
|
Sign up to set email alerts
|

circFNDC3B Accelerates Vasculature Formation and Metastasis in Oral Squamous Cell Carcinoma

Abstract: Emerging evidence has demonstrated that circular RNAs (circRNAs) are involved in cancer metastasis. Further elucidation of the role of circRNAs in oral squamous cell carcinoma (OSCC) could provide insights into mechanisms driving metastasis and potential therapeutic targets. Here, we identify a circRNA, circFNDC3B, that is significantly upregulated in OSCC and is positively associated with lymph node (LN) metastasis. In vitro and in vivo functional assays showed that circFNDC3B accelerated the migration and in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 49 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…These genes have been documented as vital agents driving tumorigenesis and promising factors with diagnostic and prognostic value throughout various human cancers including OSCC. [36][37][38][39] For example, overexpressed G6PD, PTTG1, and VEGFA in OSCC significantly associated with worse outcomes. 36,37,39 Particularly, CDK1 was frequently highly expressed across multiple cancers and promoted cancer cell proliferation and progression by facilitating cell cycle transition, cell migration, and EMT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These genes have been documented as vital agents driving tumorigenesis and promising factors with diagnostic and prognostic value throughout various human cancers including OSCC. [36][37][38][39] For example, overexpressed G6PD, PTTG1, and VEGFA in OSCC significantly associated with worse outcomes. 36,37,39 Particularly, CDK1 was frequently highly expressed across multiple cancers and promoted cancer cell proliferation and progression by facilitating cell cycle transition, cell migration, and EMT.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, our in‐silicon analyses identified 7 SRGs including CDK1, G6PD, IL1A, MAD2L1, PDCD10, PTTG1, and VEGFA which were highly expressed in primary OSCC samples and associated with patient's prognosis. These genes have been documented as vital agents driving tumorigenesis and promising factors with diagnostic and prognostic value throughout various human cancers including OSCC 36–39 . For example, overexpressed G6PD, PTTG1, and VEGFA in OSCC significantly associated with worse outcomes 36,37,39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment of OSCC includes surgery, chemotherapy, and radiotherapy, but most patients have poor prognoses 15 . The pathogenesis of OSCC is not clear 16 . It is the focus of OSCC research to clarify its pathogenesis and development mechanism at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…The global toll of 170,000 deaths and over 370,000 new cases reported in the latest Global Cancer Statistics underlines its severity 1 . Despite some strides in cancer treatment research, the prognosis for OSCC patients remains grim, with a 5‐year survival rate below 50% 2 . Urgent exploration of novel therapeutic strategies is imperative.…”
Section: Introductionmentioning
confidence: 99%